Namo mantra of Narender Modi - Pankaj, Kumar (New Delhi Diamond Pocket Books, 2013)
In this book, most of the examples are based on true life incidents. However, it is very difficult to translate the true spirit of a live presentation exactly into words. But, each story and example have been selected after a careful study and certainly convey some clear cut message to the readers. Some stories will speak to you louder than others. Some will have a deeper meaning. Some will make you cry. Some will make you laugh. Some will give you a warm feeling all over. Some may create action, reaction and chain reaction. Some may hit you right between the eyes only with some slight and right reaction. Some views and comments may compel you to think entirely about a new concept and Horizon of life. The views expressed in this book are based on true and real life experiences and also on detailed analytical studies. Further, a careful attempt has been made not to hurt the sentiments of any person irrespective of any caste, creed, gender or religions. However, it is reiterated herein again that if, on the basis of the advice given in the book, any person incurs any loss, the author, publisher and printer would disown and disclaim any liability for any such loss occurring under any circumstances, whatsoever. Readers may take decision and get advice from the book at their own risk, cost and sole discretion. The basic aim of this book is to present the unique ideas, innovative concepts and new thoughts before a common man, which may help him to lead his life peacefully, comfortable and successfully in this materialistic world. In this direction, if the author gets any success even partially in his arduous efforts, it would be an immense help and service to HUMANITY and a great prayer to ALMIGHTY GOD in a true sense.
Keywords: Prime MInister; Indian Politics